Relationship with society from a gender perspective: a study in Ecuadorian university (Práxis Educativa, 2022)
The objective of this work was to describe the actions of linkage with society or extension from a gender perspective, undertaken by the Catholic University of Cuenca, in the environment of Covid-19. From an empirical and analytical research, the case study method was applied with quantitative and qualitative techniques based on the bibliographic analysis of institutional records and reports, data collection through a structured questionnaire with a Likert Scale and an in-depth interview. The results show that the institution carries out activities to disseminate and promote the gender approach; however, there is a lack of knowledge within the university community, even in opposition to the predominant favorable responses. Likewise, the protagonism of projects in social and care areas was identified, in which there is no evidence of female representation although there is recognition. This panorama is accentuated by the absence of follow-up and control mechanisms in the linkage activities that refer to gender equality, ratifying that the university requires a system of indicators to strengthen and guide the efforts and institutional resources.Keywords: Gender. Linkage with society. Higher Education.